Analisa Pengaruh Kualitas Makanan dan Citra Merek Terhadap Keputusan Pembelian Konsumen - Fitri Wahyuni; Bukhari Usman; Irwan Safwadi (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2019)
This study aims to determine the effect of food quality and brand image on consumer purchasing decisions on Nafisah Bakery and Cake Lampineung Syiah Kuala Banda Aceh District. The independent variables in this study are food quality (X1) and brand image (X2) while the dependent variable is the purchasing decision. The population in this study is Nafisah Bakery and Cake consumers. Samples taken as many as 99 respondents using purposive sampling techniques. The data obtained were analyzed using regression analysis. This analysis includes Validity Test, Reliability Test, Multiple Linear Analysis, Hypothesis Test through Determination Coefficient Analysis, F Test and T Test. Based on the research results, the regression equation Y = 3,539 + 0,445x1 + 0,405x2. Based on statistical data analysis, the indicators of this study are valid and the variables are reliable. Food quality and brand image have an influence on purchasing decisions. Hypothesis testing using the T Test shows that food quality variables and brand image have been shown to significantly influence the dependent variable of purchasing decisions